Evaluación pertinente para la diversidad individual y cultural de los estudiantes - Mendoza Carrasco, Mariella Victoria (2011)
Through the time, the evaluation has to break with established paradigms in the educational system. Currently, evaluation must be considered as an improvement process and not as a sanction mean, considering it as a dynamic, continuous, permanent, systematic, and analysis process of interpretation and information assessment. By this evaluation view, the process is centered on the student than in the teacher, which might be related to the personal development. lt is has to be considered that the evaluation is a whole moment, in which teacher and student can evaluate, considering the different learning styles and the multicultural factor of the student. The evaluation will get sense in a quality framework, whenever the efficacy and efficiency of the teacher role are proved in front of the student to be evaluated, in ali their dimensions and in an integral aspect.